Improving the sustainability of tilapia cage farming in Brazil: An emergy approach - David, Luiz Henrique Castro [UNESP]; Pinho, Sara Mello [UNESP]; Garcia, Fabiana [UNESP] (Elsevier, 2018)
The accelerated and disorderly expansion of aquaculture can lead to economic, social, and environmental problems. In this sense, it is necessary to prioritize the adoption of practices that aim for sustainable production. The aims of the present study were to identify the contributions from nature and economy in the system of tilapia cage farming. In addition, emergy accounting was utilized to evaluate whether the use of periphyton as a complementary food and the reduction of storage density improve the sustainability of this production system. Three different production managements were evaluated and compared: using traditional stocking density adopted by farmers (80 kg/m3) with 100% of the daily recommended feed and without substrates for periphyton (TRAD); traditional stocking density (80 kg/m3) with 50% of the daily recommended feed and with substrates for periphyton (TDS); lower density (40 kg/m3) with 50% of the daily recommended feed and with substrates for periphyton (LDS). We calculated using emergy accounting the transformity (Tr), renewability (%R), emergy yield ratio (EYR), emergy investment ratio (EIR), emergy loading ratio (ELR), emergy exchange ratio (EER), and emergy sustainability index (ESI) of the distinct production managements. The results showed that tilapia cage farming is highly dependent on resources from economy, and feed is mainly responsible for this. Thus, the decrease in stocking density and feed rate, combined with the use of periphyton, improved all emergy indices evaluated. This occurred because there was a decrease in the use of resources from economy and increase in the use of renewable natural resources. The study shows through the emergy accounting that the use of periphyton to feed cultured fish combined with a reduction in artificial feed use and a decrease in the stocking density should be encouraged to promote the sustainability on tilapia cage farming.
Keywords: Aquaculture; Commercial feed; Density stocking; Emergy; Periphyton